2010
DOI: 10.1097/wnn.0b013e3181c5e2e5
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian Version of the Addenbrooke Cognitive Examination-revised in the Diagnosis of Mild Alzheimer Disease

Abstract: The Brazilian version of the ACE-R displayed high diagnostic accuracy for the identification of mild AD in the studied sample.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
1
11

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 35 publications
5
57
1
11
Order By: Relevance
“…Cutoff points for the full battery of tests and the MMSE (ACE-R) were set at <78 points and <25 points, respectively. 11 The aim of the digit span task is to assess the short-term storage capacity of the memory and its executive component, particularly when the digits are counted in reverse order. 12 The Beck Anxiety inventory (BAI) was used to record symptoms of anxiety.…”
Section: Assessment Of the Subjectsmentioning
confidence: 99%
“…Cutoff points for the full battery of tests and the MMSE (ACE-R) were set at <78 points and <25 points, respectively. 11 The aim of the digit span task is to assess the short-term storage capacity of the memory and its executive component, particularly when the digits are counted in reverse order. 12 The Beck Anxiety inventory (BAI) was used to record symptoms of anxiety.…”
Section: Assessment Of the Subjectsmentioning
confidence: 99%
“…Within this sum there are 30 points referring to the MMSE score. A recent study confirmed that the Brazilian version of the ACE-R maintains high accuracy in identifying Alzheimer's disease, when the cutoff point is set at 78 (16) . To screen for anxiety symptoms, the Beck Anxiety Inventory (BAI), validated in Brazil (17) , which consists of a list of 21 common anxiety symptoms, with four alternatives each, in increasing order of anxiety level.…”
Section: Study Protocolmentioning
confidence: 85%
“…And the exclusion criteria were auditory or visual disabilities that hindered communication and application of the tests; presence of cognitive deficit, measured using the ACE-R (15)(16) , with a score inferior to 78 point; and participation in the entire program (including the initial and final assessments).…”
Section: Population or Sample: Inclusion And Exclusion Criteriamentioning
confidence: 99%
“…The overall ACE-R score ranges from 0 to 100 points, distributed among the five domains: attention/ orientation (18 points), memory (26 points), verbal fluency (14 points), language (26 points) and visuospatial skills (16 points) (19) . We chose to use the median according to education level for the cut-off score of the ACE-R instrument, considering the high percentage of elderly with low educational level and the lack of a standard in the literature for this profile in the population.…”
Section: Methodsmentioning
confidence: 99%